The Development of Learning Media Using Interactive Jobsheets for Basic Subjects in Electricity and Electronics Using PSIM in Tamansiswa Vocational High School - Hidayat, Nurul (Journal of Vocational Education Studies, 2020)
This study aims to develop learning devices for the subjects of Elementary Electricity and Electronics in class X. As long as learning in class does not provide practical activities, it is necessary to develop learning devices equipped with practical activities as soon as possible.This study uses a 4-D model development model. This study consisted of 2 classes with 1 non-experimental class and 1 experimental class.The rating results show the percentage of 96% so that it can be concluded that the learning device meets eligibility. The results of sample t-test correlate results obtained are 39.480, the value of t table is 2.045. The rating results indicate the percentage of 88% so that it can be concluded that the learning tool helps students carry out learning activities and practicum. The results of t-test on 2 independent samples obtained 4.420, the value of t table is 2.045.